Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Perusahaan Daerah Air Minum (PDAM) Kota Padang - Muhammad Hendra (JURNAL PUNDI, 2021)
ABSTRACTThis study aims to determine the effect of work environment and work discipline either partially or simultaneously on employee performance in pdam padang. The population in this study are employee of pdam padang, amounting to 271 people with a total sample of 73 poeple using the slovin formula. Based on the research reults, the work environment and work discipline partially positive significant effect the pdam padang because the regression coefficient is positive. Ie b1 = 0.543 and sig value 0,000 is smaller than level of significant (α) 0.05. Work environment significantly positively effect the employee performance because the regression coefficient is positive, ie b2 = 0.642 and sig value 0,000 is smaller than level of significant (α) 0.05. Work discipline simultaneously significantly effect the employee performance because of sig 0.000 which is smaller than the level of significant (α) 0.05 and 37.2% of employee performance which is influenced by the working environment and working discipline, while 62.8% of employee performance is influenced by variables other than the models studied which are apart from the working environment and working discipline.Keyword: Environment, Diciplin, Performance